Indonesian Police Failure in The Sukatani Crisis: An Application of Benoit’s Image Repair Theory - Santika, Azzumar Adhitia; Fawzy, Dwimay (Universitas Brawijaya, 2025)
The Indonesian Police have faced challenges in handling the crisis of intimidation involving the Sukatani band. This study employs quantitative content analysis of 32 news reports to identify communication strategies used by the police, as reported in the media. To support this analysis, semi-structured interviews were also conducted with 10 participants from diverse backgrounds—including lecturers, civil servants, employees, a political activist, a teacher, an artist, and an entrepreneur. Although limited in number, the participants’ responses showed consistent patterns, making their input sufficient to support the main analysis. These responses were used to enrich interpretation, as we also used reports from reputable organizations as other secondary data to draw generalizable conclusions. The findings show that the police failed to implement several strategies effectively due to low public trust and inconsistencies in applying the denial strategy, which undermined the success of subsequent efforts. In response, this study proposes a model combining corrective action and mortification strategies with transformational leadership to regain public trust. The model highlights the importance of strengthening leader-follower relationships to prevent similar crises. The Sukatani case—along with other crises of police misconduct—demonstrates that the current transformation process remains ineffective, underscoring the need for more concrete and holistic institutional reform.